(3GdcGTa aj eYQaI CSeGA GdQLGds - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3GdMGaX GdeRj , jhSa Hf YHO GdQMef Hf jhSa LeGd GdOjf GdRcj CHh eMeO GdbVGYj GdcdHj, LeGd GdOjf CHh GdMLGL GdMGaX GdeRj,J (B742 (3g` s ((3GHf GdaJM GdSHci (B( (3Jbi GdOjf eMeO Hf YHO GddWja GdSHci (B) s)
(3ChdgG (B:s
(3GdMeO ddg hGdTcQddg h Mhd hdG bhI EdG HGddg gPG eNJUQ fGaY ai QLGd GdcJH GdSJg s
(3BNQgG (B:s
(3bGdJ CHj SGFQ CRhGL GdfHi Udi Gddg Ydjg hSde s
(3GfXQ Qbe (B" 387" (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJGQjNs